Korelasi antara Tartib Al-Ayat dan Fawatih Al-Suwar dalam Struktur Al-Qur’an - Mutmainnah, Andi; Syam, Arham Fajrul; Abubakar, Achmad; Abdullah, Dudung (Al Karima : Jurnal Studi Ilmu Al Quran dan Tafsir, 2024)
This research aims to understand the structure of the preparation of the Al-Qur’an by looking at the tartib al-ayat and fawatih al-suwar with several problematic methods. Regarding the method of compiling the Qur’an, there are several opinions that use the tauqifi method, ijtihad, or combine the two, tauqifi and ijtihad of the Companions. So in this article we will discuss in more depth about tartib al-ayat and fawatih al-suwar in the structure of the preparation of the Qur’an. The methodology used is qualitative, namely emphasizing analysis on the deductive inference process. The data analysis used in this writing is a comprehensive analysis known as manhaj tahlili, which means analyzing the interpretation in depth of various linguistic elements and elements of rules. The results of the research are that the systematic arrangement of verses and surahs of the Koran is tauqifi, that is, it is the prerogative of Allah SWT. Allah has instructed his apostle through revelation which places each verse in a letter in a position that corresponds to the events that occurred during the time of the apostle. So, the arrangement of the verses of the Qur’an is tauqifi in accordance with the statements put forward regarding the arrangement of verses in the Qur’an based on the instructions set by the Prophet.